Book embedding of graph bundles over a cycle with claw as a fibre - Shao, Zeling; Qi, Chenyang; Li, Zhiguo (Utilitas Mathematica, 2020)
A book embedding of a graph G consists of setting the vertices in a line which called spine and assigning the edges in half planes so that edge assigned to the same page without crossing. The minimum number of half planes needed in a book embedding of a graph is called its page number. Graph bundles generalize the notion of covering graphs and Cartesian products of graphs. In this paper, the page number of product bundles over a cycle with claw as a fibre with respect to the Cartesian and direct product are determined except of one case about Cartesian product. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.